'Am I Still One of Them?': Bicultural Immigrant Managers Navigating Social Identity Threats When Spanning Global Boundaries. (6th February 2017) - Kane, Aimée A.; Levina, Natalia
Abstract: We examine the practice of nominating bicultural immigrants to manage knowledge‐intensive projects sourced from their host to their home countries. We focus on their actions vis‐à‐vis global collaborators and unpack psychological processes involved. Managers in these positions have to navigate the workplace social identity threat that arises from being associated with the home country group – a lower status group in this context. How they navigate this threat shapes the way they use their bicultural competencies and authority as managers. When they embrace their home country identity, immigrant managers tend to enable knowledge‐based boundary spanning through actions empowering home country collaborators, such as teaching missing competencies, connecting to important stakeholders, and soliciting input. Instead, when distancing from their home country identity, they tend to hinder collaborators by micromanaging, narrowing communication channels, and suppressing input. We develop theoretical implications for the study of global boundary spanning, bicultural managers, and workplace social identity.